Polycyclic aromatic hydrocarbons in primary school environments: Levels and potential risks - Oliveira, M (2017)
Although polycyclic aromatic hydrocarbons (PAHs) are priority air pollutants that strongly affect human health, information concerning the indoor exposures is still limited. This study characterized PAH levels in primary schools and evaluated risk for the respective students (aged 8-10 years) in comparison with school personnel. During January-April 2014, eighteen particulate-bound (PM2.5) PAHs (16 USEPA priority compounds, dibenzo[a, l]pyrene, benzo[j]fluoranthene) were collected (indoors and outdoors) at ten primary urban schools in Portugal. Total mean concentrations (Sigma(PAHs)) ranged 2.8-54 ng m(-3) in indoor air, whereas corresponding outdoor levels were 7.1-48 ng m(-3). Indoor/outdoor ratios of lighter congeners (2-3 aromatic rings) demonstrated a contribution from indoor origin while heavier PAHs (4-6 aromatic rings) originated mostly from infiltration of ambient air indoors; traffic (both from diesel and gasoline fuelled vehicles) was the predominant source of indoor PAHs. Total cancer risk of 8-10 years old children exceeded (up to 22 times) USEPA recommended guideline of 10(-6), and 7-87 times WHO health-based threshold of 10(-5). Risk due to indoor exposure in schools was 2-10 times higher than outdoors, mainly because of the higher amount of time that students spent indoors.